The Dawn of the BioGeoSCAPES Program: Ocean Metabolism and Nutrient Cycles on a Changing Planet - Mak Saito; Harriet Alexander; Heather Benway; Philip Boyd; Martha Gledhill; Elizabeth Kujawinski; Naomi Levine; Mairead Maheigan; Adrian Marchetti; Ingrid Obernosterer; Alyson Santoro; Dalin Shi; et al. (Oceanography, 2024)
Biogeochemical cycles constitute Earth’s life support system and distinguish our planet from others in this solar system. Microorganisms are the primary drivers of these cycles. Understanding the controls on marine microbial dynamics and how microbes will respond to environmental change is essential for building and assessing model-based forecasts and generating robust projections of climate change impacts on ocean productivity and biogeochemical cycles. An international community effort has been underway to create a global-scale marine microbial biogeochemistry research program to tackle gaps in this understanding. The BioGeoSCAPES: Ocean Metabolism and Nutrient Cycles on a Changing Planet program will identify and quantify how marine microbes adjust to a changing climate and assess the consequences for global biogeochemical cycles. This article summarizes the ongoing efforts to launch BioGeoSCAPES.